2009
DOI: 10.1097/ftd.0b013e31819c3d6d
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Variability in Tacrolimus Pharmacokinetics to Optimize Early Exposure in Adult Kidney Transplant Recipients

Abstract: To prevent acute rejection episodes, it is important to reach adequate tacrolimus (TRL) exposure early after kidney transplantation. With a better understanding of the high variability in the pharmacokinetics of TRL, the starting dose can be individualized, resulting in a reduction in dose adjustments to obtain the target exposure. A population pharmacokinetic analysis was performed to estimate the effects of demographic factors, hematocrit, serum albumin concentration, prednisolone dose, TRL dose interval, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
131
4
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 47 publications
10
131
4
2
Order By: Relevance
“…Differences in the distribution of PXR SNPs were found when comparing the Han Chinese of South China and Caucasian Americans [31] . PXR -25385C>T, an SNP located in the PXR promoter and found to be correlated with CYP3A4 phenotype, was identified as a significant covariate for apparent oral clearance (CL/F) of tacrolimus by Benkali et al [32] , but this result could not be replicated in another study [33] . Cytochrome P450 oxidoreductase (POR) is known as the obligatory electron donor in the metabolism of drugs by CYP enzymes in humans, and the correlation between POR genetic polymorphisms and CYP-catalyzed drug metabolism has become a research hot spot.…”
Section: Tacrolimusmentioning
confidence: 55%
“…Differences in the distribution of PXR SNPs were found when comparing the Han Chinese of South China and Caucasian Americans [31] . PXR -25385C>T, an SNP located in the PXR promoter and found to be correlated with CYP3A4 phenotype, was identified as a significant covariate for apparent oral clearance (CL/F) of tacrolimus by Benkali et al [32] , but this result could not be replicated in another study [33] . Cytochrome P450 oxidoreductase (POR) is known as the obligatory electron donor in the metabolism of drugs by CYP enzymes in humans, and the correlation between POR genetic polymorphisms and CYP-catalyzed drug metabolism has become a research hot spot.…”
Section: Tacrolimusmentioning
confidence: 55%
“…In addition, tacrolimus is also highly metabolized by CYP3A5. 5 The peri-transplant period is characterized by the administration of numerous drugs that can affect the cytochrome P450 system and alter tacrolimus clearance. Population pharmacokinetic studies in HSCT recipients have shown that liver or kidney impairment can result in decreased tacrolimus clearance and increased blood tacrolimus concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in this multi-center randomized controlled trial, patients receiving tacrolimus daily dose according to their CYP3A5 genotype, achieved the target concentration more rapidly with lesser dose modification and in an higher percentage ( >75%) when compared to those in whom tacrolimus was managed with a concentrationcontrol strategy [21]. ABCB1 polymorphisms do not seem to influence tacrolimus pharmacokinetic and research into this association has yielded mixed results [22,23]. Nevertheless, in our series we observed a significant reduction in tacrolimus concentration and dose-adjusted tacrolimus concentrations in the early post-transplant period for the TT polymorphism of C1236T; this suggests that there is higher metabolism of the drug in subjects with this genotype [24].…”
Section: Cyp3a5 and Abcb1 Genotypes And Tacrolimusmentioning
confidence: 99%